2015
DOI: 10.2217/rme.15.2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Yield of Endothelial Cells from Peripheral Blood for Cell Therapies and Tissue Engineering

Abstract: Aim Peripheral blood-derived endothelial cells (pBD-ECs) are an attractive tool for cell therapies and tissue engineering, but have been limited by their low isolation yield. We increase pBD-EC yield via administration of the chemokine receptor type 4 antagonist AMD3100, as well as via a diluted whole blood incubation (DWBI). Materials & Methods Porcine pBD-ECs were isolated using AMD3100 and DWBI and tested for EC markers, acetylated LDL uptake, growth kinetics, metabolic activity, flow-mediated nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Autologous circulating endothelial progenitor cells were isolated and cultured from peripheral mononuclear cells of the oral mucosal samples of each experimental rat using a diluted whole blood incubation technique, as previously described 23 , 39 . Peripheral blood from the same rat was obtained and anticoagulated with 20-USP heparin units/mL blood (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous circulating endothelial progenitor cells were isolated and cultured from peripheral mononuclear cells of the oral mucosal samples of each experimental rat using a diluted whole blood incubation technique, as previously described 23 , 39 . Peripheral blood from the same rat was obtained and anticoagulated with 20-USP heparin units/mL blood (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…1 ). Endothelial progenitor cells can be isolated from peripheral blood cells 22 , 23 . The pre-vascularized layer beneath the keratinocyte layer contained pre-formed microvessels generated by isolating and expanding endothelial cells from peripheral blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fibroblasts produce collagen fibres and replace fibrin matrix, contributing to a coherent three-dimensional cell-sheet structure 22 , 23 . Further, the cell sheets included pre-formed microvessels derived from the EPC isolated from adult peripheral blood monocytes as reported previously 17 , 24 . The pre-formed microvessels might have contributed to the early survival of the tissue-engineered cell sheets in the wound bed by ensuring sufficient blood supply, resulting in accelerated wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…6 We further showed that the oral mucosal cell sheets might have the necessary tissue plasticity for promoting rapid and scarless cutaneous wound healing, with in vivo effects equivalent to skin-derived cell sheets in a rat skin wound model. 9,10 The in vivo examinations of the prevascularized oral mucosal cell sheet might guide the clinicians to potentially use the cell sheet engineering from the oral mucosa in the patients with cutaneous burn wounds. 8 The cell sheets include the preformed microvessels from the endothelial progenitor cells isolated from adult peripheral blood monocyte cells as reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…8 The cell sheets include the preformed microvessels from the endothelial progenitor cells isolated from adult peripheral blood monocyte cells as reported previously. 9,10 The in vivo examinations of the prevascularized oral mucosal cell sheet might guide the clinicians to potentially use the cell sheet engineering from the oral mucosa in the patients with cutaneous burn wounds. Therefore, we examined the potential use of our newly developed prevascularized oral mucosal cell sheet in skin excisional wounds.…”
mentioning
confidence: 99%